Equilibrium vitrification of mouse embryos at various developmental stages using low concentrations of cryoprotectants - Juan QIU; Kazutsugu MATSUKAWA; Chihiro KOSHIMOTO; Keisuke EDASHIGE (The Society for Reproduction and Development, 2021)
We previously developed a new vitrification method (equilibrium vitrification) by which two-cell mouse embryos can be vitrified in liquid nitrogen in a highly dehydrated/concentrated state using low concentrations of cryoprotectants. In the present study, we examined whether this method is effective for mouse embryos at multiple developmental stages. Four-cell embryos, eight-cell embryos, morulae, and blastocysts were vitrified with EDFS10/10a, 10% (v/v) ethylene glycol and 10% (v/v) DMSO in FSa solution. The FSa solution was PB1 medium containing 30% (w/v) Ficoll PM-70 plus 0.5 M sucrose. The state of dehydration/concentration was assessed by examining the survival of vitrified embryos after storage at -80°C. When four-cell embryos and eight-cell embryos were vitrified with EDFS10/10a in liquid nitrogen and then stored at -80°C, the survival rate was high, even after 28 days, with relatively high developmental ability. On the other hand, the survival of morulae and blastocysts vitrified in liquid nitrogen and stored at -80°C for four days was low. Therefore, morulae and blastocysts cannot be vitrified in a highly dehydrated/concentrated state using the same method as with two-cell embryos. However, when blastocysts were shrunken artificially before vitrification, survival was high after storage at -80°C for four days with high developmental ability. In conclusion, the equilibrium vitrification method using low concentrations of cryoprotectants, which is effective for two-cell mouse embryos, is also useful for embryos at multiple stages. This method enables the convenient transportation of vitrified embryos using dry ice.